A TUTOR'S EFFORTS IN IMPROVING STUDENTS' LEARNING COMPREHENSION IN PURSUING PACKAGE C THROUGH THE USE OF PARTICIPATORY LEARNING METHODS: UPAYA TUTOR DALAM MENINGKATKAN KETUNTASAN BELAJAR PESERTA DIDIK KEJAR PAKET C MELALUI PENGGUNAAN METODE PEMBELAJARAN PARTISIPATIF - Dini Puji Astuti, Puji (LPPM Universitas Ibn Khaldun, Bogor, 2024)
Application of Participatory Teaching and Learning Methods as an alternative in helping to solve the problems experienced by students in the learning process of Islamic Religious Education Subjects. This study aims to improve the learning completeness of Package C Pursuing Group Students at PKBM Bintang Tunas Mulia in the subject of Islamic Religious Education. The type of research used in this research is Classroom Action Research, in which there are two cycles. Each cycle is held in two meetings according to the hours stated in the lesson plan. In each cycle there are stages which include planning, implementation of action (application of participatory learning methods), observation and finally reflection. The research subjects in this study were package C students who had learning mastery problems as many as 15 students. The results of the study showed that in the first cycle of research, only 10 students or 66.66% were able to achieve KKM scores so that they were said to be complete in learning from 15 students. Classically the 10 students have fulfilled the average value obtained of 64.66 or are in the low category. Whereas in cycle II of 15 students there were 14 people or 93.66% who met the minimum completeness (KKM) of 85 or were in the highest category.